Role of family in children upbringing - Vlasova Y. Y. (Priority directions of scienceand education development, 2016)
the article discusses the main factors of family's role pedagogical importance in upbringing and formation of the child as an individual.
Keywords: дети; Семья; обучение; развитие; роль; training; family; children; development; важность; importance; Role